2016
DOI: 10.21608/epsj.2016.5419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Selection for Body Weight, Keel Length and Breast Circumference on Egg Production Traits in Inshas Strain of Chickens

Abstract: Inshas strain of chicken was subjected to one cycle of early selection for body weight, keel length and breast circumference effect on egg production traits. Best linear unbiased prediction (BLUP) was used for predicting the breeding values and ranking then selecting hens. The selection differentials in G1 were equal to 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 8 publications
3
11
1
Order By: Relevance
“…These approaches may lead to some undesirable consequences such as disease outbreaks, increased stress, fat accumulation, leg problems, and metabolic disorder. From a nutritional point of view, dietary modulation represents a remarkable way of modifying animals' performance and well-being ( Abou El-Ghar and Abd El-Karim, 2016 ; Akbari et al., 2016 , 2018 ; Fathi et al., 2016 ; El-Senousey et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…These approaches may lead to some undesirable consequences such as disease outbreaks, increased stress, fat accumulation, leg problems, and metabolic disorder. From a nutritional point of view, dietary modulation represents a remarkable way of modifying animals' performance and well-being ( Abou El-Ghar and Abd El-Karim, 2016 ; Akbari et al., 2016 , 2018 ; Fathi et al., 2016 ; El-Senousey et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abdellatif and EL-Hammady (1992) indicated the genetics of sexual dimorphism in Dandarawi chickens, where males body weight were heavier than females within the same age and at different ages.The direct response or the genetic gain in a selected trait could be determined by the difference between the mean of selected group and population means (Falconer, 1981). The direct response due to selection for high body weight over generations was reported by Abdellatif (1999) and Abou El-Ghar and Abd El-Karim (2016). The main objectives of the present study were to determine the direct effect due to selection for high body weight at eight weeks of age on body weight and body conformation measurementsover two generations at different ages in Dandarawi chicken.…”
Section: Introductionmentioning
confidence: 59%
“…Body weight is usually consideringa fair indicator for subsequent growth rate (Chambers, 1990). As reported before in different selection programs, there were significant differences between lines selected for high and low body weight at 8 weeks of age (Maloney et al 1967;Marks, 1983;Liu et al 1995;Abdellatif, 1999;EL-Dlebshany, 2004;Abd El-Karim and Ashour, 2014;Ashour et al 2015and Abou El-Ghar andAbd El-Karim, 2016). As for the effect of sex on body weight (Maloney et al 1967;Jaap, 1971;Soltan andEL-Nadi, 1986 andAbdellatif, 1989) reported that the males body weight at 8 weeks of age was superior that of females with significant differences.The individual selection is effective for certain traits that exhibited high heritability estimates such as body weight (Rishell, 1997).Many of body conformation measurements such as shank and keel lengths may be used as good indicators for skeletal size, where Chambers(1990) stated that there were genetic relationship between growth and skeletal dimensions.Normally the sexual dimorphism occurs in the majority of the domesticated avian species, especially in the chickens where the males were found to be heavier than females by about 10-20% as Merritt (1966) and Buvanendran (1969).…”
Section: Introductionmentioning
confidence: 61%
“…One hundred and twenty birds of the local Egyptian strain Inshas, aged 24 weeks old, were used in this study. The average age of sexual maturity for Inshas hens is 22–25 weeks of age [ 18 ]. At the start of the experiment, all birds were weighed individually to the nearest gram and then distributed into four groups and randomly replicated.…”
Section: Methodsmentioning
confidence: 99%